1999
DOI: 10.1074/jbc.274.17.11535
|View full text |Cite
|
Sign up to set email alerts
|

p53 Down-regulates Human Matrix Metalloproteinase-1 (Collagenase-1) Gene Expression

Abstract: We hypothesize that the abnormality of p53 seen in RA synovium may contribute to joint degeneration through the regulation of human matrix metalloproteinase-1 (hMMP-1, collagenase-1) gene expression. Transcription assays were performed with luciferase reporters driven by the promoter of the hMMP-1 gene or by a minimal promoter containing tandem repeats of the consensus binding sequence for activator protein-1, cotransfected with p53-expressing plasmids. The results revealed that (i) wild-type (wt) p53 down-reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
107
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(113 citation statements)
references
References 44 publications
6
107
0
Order By: Relevance
“…For example, the p53 status of the tumor could influence the levels of MMP-1 as it has been shown that wild-type p53 suppresses MMP-1 transcription. [31][32][33] Brinckerhoff et al 34 propose a model that addresses the likelihood of the 2G allele contributing to pathologic processes. The model states that several molecular events must take place in addition to the presence of the 2G allele.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the p53 status of the tumor could influence the levels of MMP-1 as it has been shown that wild-type p53 suppresses MMP-1 transcription. [31][32][33] Brinckerhoff et al 34 propose a model that addresses the likelihood of the 2G allele contributing to pathologic processes. The model states that several molecular events must take place in addition to the presence of the 2G allele.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, BAI1 inhibition of interstitial collagenase expression may prevent the dissolution of the extracellular matrix. Matrix metalloproteinase-1 (MMP-1) was found in other cells to be a p53-target gene, subject to p53 repression, mediated in part by associated protein 1 (Sun et al, 1999). We are currently investigating the MMP-1 protein level and activity in relation to BAI1 and p53 expression.…”
Section: Discussionmentioning
confidence: 99%
“…These data suggest that a subset of synovial fibroblasts may possess an inactive form of p53. Overexpression of plasmids encoding the p53 mutants found in RA synovium suppresses wild-type p53 function, as indicated by the induction of known p53-regulated genes, including IL-6 (53,54) and MMP-1 (55,56), which are normally inhibited by wild-type p53. Additionally, mice deficient in p53 display enhanced experimental arthritis, elevated levels of IL-6 in the synovium, and increased spontaneous MMP-13 expression compared with wildtype mice (57).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, p21-deficeint synovial fibroblasts behave similarly to the RA synovial fibroblasts that lack p53 or express the mutant forms of p53. Furthermore, ectopic expression of p21 or overexpression of wild-type p53 reduces IL-6 and MMP-1 expression in RA synovial fibroblasts (53)(54)(55)(56)58). Collectively, these data suggest that p21 may be one of the nodal points through which p53 inhibits cytokines and MMPs (Fig.…”
Section: Discussionmentioning
confidence: 99%